2018
DOI: 10.1017/s003329171800332x
|View full text |Cite
|
Sign up to set email alerts
|

Risk and coaggregation of major psychiatric disorders among first-degree relatives of patients with bipolar disorder: a nationwide population-based study

Abstract: BackgroundBipolar disorder is a highly heritable mental illness that transmits intergeneratively. Previous studies supported that first-degree relatives (FDRs), such as parents, offspring, and siblings, of patients with bipolar disorder, had a higher risk of bipolar disorder. However, whether FDRs of bipolar patients have an increased risk of schizophrenia, major depressive disorder (MDD), autism spectrum disorder (ASD), and attention deficit hyperactivity disorder (ADHD) remains unclear.MethodsAmong the entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 26 publications
4
52
0
Order By: Relevance
“…Overall, findings from the study were in line with prior clinical 5,6 and epidemiological studies, [7][8][9][10] hereby confirming the validity of the register-linkage methodology of the present study. It is of interest that our findings also seem to apply outside of Scandinavian as the recent study from Taiwan 10 had similar findings.…”
Section: General Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, findings from the study were in line with prior clinical 5,6 and epidemiological studies, [7][8][9][10] hereby confirming the validity of the register-linkage methodology of the present study. It is of interest that our findings also seem to apply outside of Scandinavian as the recent study from Taiwan 10 had similar findings.…”
Section: General Findingssupporting
confidence: 90%
“…5 The variation is likely due to heterogenous designs, methods and generally small and selected sample sizes (up to a few hundred first-degree relatives, with a few exceptions 5 ) and varying lengths of the follow-up periods. 6 Further, few epidemiological studies have targeted first-degree relatives to patients with bipolar disorder [7][8][9][10] and there is a lack of epidemiological studies that systematically have investigated rates of psychiatric disorders in high-risk individuals during lifetime. With the increasing focus on risk and resilience (the capacity to resist) in mental health, 11 it is specifically important to map the risk of developing psychiatric disorders during lifetime.…”
mentioning
confidence: 99%
“…For example, offspring of patients affected with psychosis, bipolar disorder or depression have a greater risk of developing these disorders (32% by adulthood) 121,122 . Monozygotic twins [123][124][125][126] and first-degree relatives (depending on the number of probands) [127][128][129][130] also have an increased likelihood of developing these disorders. However, only 17.4% of the association between family history of psychosis and the disorder is mediated through a modelled polygenic risk score 131 .…”
Section: Genetic Factorsmentioning
confidence: 99%
“…First‐degree relatives (one proband: RR=6.10, two probands: RR=29.1) 128 *…”
Section: Evidence Supporting Primary Prevention and Mental Health Promotion In Young Peoplementioning
confidence: 99%
“…We therefore assume that NHI data may be more reflective of patients' naturalistic course of treatment seeking in medical settings and the degree of physicians' recognition of eating disorders. Studies using Taiwan's NHI database have expanded rapidly in both quantity and quality across many fields, including psychiatry (Chen et al, 2019; Huang et al, 2020; Wu, Liao, Tsai, Chang, & Tsai, 2017), since the first study was published in 2000 (Chen et al, 2011; Hsieh et al, 2019). Despite fundamental problems (e.g., improvement in the validity of the database), one recently published study reported that the accuracy of the diagnostic codes for major depressive disorder, schizophrenia, and dementia were acceptable, although the accuracy for bipolar disorder and minor depression were less satisfactory (Wu, Kuo, Su, Wang, & Dai, 2020).…”
Section: Introductionmentioning
confidence: 99%